As potencialidades do uso do aplicativo GraphoGame para os estudantes com deficiência intelectual - Silva, Cristiane Gonçalves da (2023)
This study, linked to the Special Education, Inclusion and Difference research line of the Postgraduate Program in Education (PPGE) and the Interdisciplinary Research Group in Education, at the Federal University of Santa Maria, starts from the following guiding question: how does GraphoGame Does it contribute to the learning of students with Intellectual Disabilities? Therefore, the general objective is to analyze the potential of using GraphoGame in the learning of students with Intellectual Disabilities. The methodology is characterized as qualitative research, of a basic nature, exploratory and descriptive and in terms of methodological procedures as participatory research. The subjects are students with intellectual disabilities, who attend the Specialized Educational Service, from the 2nd to the 7th year of Elementary School, aged between seven and fifteen. For data collection, participant observation will be used, through the field diary, where students will be observed while applying the GraphoGame game. The data will be produced using the Intera methodology, which consists of: Pre-Assessment (Phonological Awareness Assessment Test - Form A), Application Application (Interactions with the GraphoGame game) and Post-Evaluation (Phonological Awareness Assessment Test - Form B). The analysis of the results of this investigation will be a qualitative analysis. The study is important because it presents results related to the use of the GraphoGame application in the learning of students with intellectual disabilities, considering the potential in the reading processes. With this, it will be able to contribute to remedying the lack of research that proves the effectiveness of using the application in Brazil, a country that is part of the world ranking in downloads. Finally, it can be seen from the discussion of the results and data analysis that the GraphoGame application is a potential learning tool to assist teachers in their planning during the literacy process for students with Intellectual Disabilities. It can contribute to the development of phonological awareness and stimulate the act of learning through its technological, playful and pleasurable characteristics.